What factors are associated with early childhood dental caries? A longitudinal study of the Growing Up in New Zealand cohort. Issue 3 (20th July 2020) - Thornley, Simon; Bach, Katie; Bird, Amy; Farrar, Rachel; Bronte, Sarah; Turton, Bathsheba; Atatoa Carr, Polly; Fa'alili‐Fidow, Jacinta; Morton, Susan; Grant, Cameron
Abstract: Background: The relative importance of different strategies to prevent dental caries is not known. Aim: We explored the relationship between oral health behaviours, diet, and the incidence of dental caries. Design: We conducted a study of children participating in the 'Growing Up in New Zealand' cohort. Exposures were oral health behaviours, a food frequency questionnaire, and sociodemographic characteristics that were recorded when the child was nine months and two years old. Outcomes were records of dental caries at ages four to seven years. Results: 4111 children had dental examination records from between the ages of four and seven years. High levels of dental caries were reported in children of Pacific, Asian, and Māori ethnicity. Food frequency questionnaire information was summarised into two principal components. The major axis of variation was in the intake of food and drinks with high concentrations of sugar and refined starch, with this component strongly associated with caries (multivariable incidence rate ratio of caries 0.48; 95% confidence interval: 0.38‐0.61, comparing the extreme quintiles of the first principal component). Conclusions: A diet high in sugar or refined starch was strongly linked to caries. Policies to reduce sugar and refined starch intake should be considered.